OP0087 Infliximab plus methotrexate inhibits structural damage, reduces sign and symptoms and improves disability in patients with active early rheumatoid arthritis. (1st June 2001) - Emery, P; Maini, R; Breedveld, F; Smolen, J; Kalden, J; Van der Heijde, D; Han, C; Harriman, G
Abstract : Background: In the ATTRACT trial, 428 pts with active RA despite methotrexate (MTX) therapy received MTX alone or infliximab at 3 mg/kg or 10 mg/kg every 4 or 8 weeks along with MTX for 102 weeks. Since joint damage may progress rapidly early in the disease course, pts with early RA (disease duration < = 3 yrs) were analysed. In this study, 82 of 428 pts (17 placebo, 19 in each of the 3 mg/kg infliximab group, 20 in the 10 mg/kg q8 group and 7 in the 10 mg/kg q4 group) had early RA. Objectives: To determine prevention of structural damage, reduction in signs and symptoms and improvement in disability in pts with early RA after two years of treatment. Methods: Structural damage was assessed using the Van der Heijde modification of the Sharp score (TSS). Radiographs of hands and feet were obtained at baseline, and after 30, 54 and 102 weeks. Two trained readers scored the films independently. The mean score of the two readers for each set of radiographs was used for further analysis. A clinical response was defined as an ACR 20 response at week 102. Disability was assessed by analysing patients? weighted mean change from baseline HAQ scores through week 102. The changes in TSS and HAQ score from baseline to week 102 were compared between the infliximab treatment groups and the placebo group by using analyses of variance of van der Waerden normal scores. The proportions of pts with a clinical response at week 102 were compared by using chi-square test. Results: The change in TSS from baseline through week 102 was significantly lower in each infliximab dose regiments compared to placebo, as shown in the Table 1 . The clinical response rate was 29% for the placebo group, 37% for the 3 mg/kg q8 group, 53% for the 3 mg/kg q4 group, 45% for the 10 mg/kg q8 group and 43% for the 10 mg/kg q4. The median improvement in HAQ was 0.2 for the placebo group, 0.2 for the 3 mg/kg q8 group, 0.5 for the 3 mg/kg q4 group, 0.4 for the 10 mg/kg q8 group and 0.5 for the 10 mg/kg q4. The results for clinical response and HAQ did not reach statistical significance. However, they are consistent with the results of overall study population. Conclusion: Treatment through 102 weeks with any of the 4 infliximab regimens plus MTX, inhibits structural joint damage. Early intervention with infliximab in pts with active disease despite MTX may protect joints during the early, rapidly-progressive, destructive phase of the disease.